Bogotá Utopic: Urban Planning and Public Order in the Building of Colombia, 1948–1853 - Waterhouse, Amanda C. (Comparativ, 2020)
This article examines an urban planning project for Bogotá, Colombia, that foreign planners formulated after large-scale riots of April 1948. The Bogotazo propelled elite fears of popular revolt, aligning United States anticommunist interests with the public order concerns of the Colombian government. These state actors looked to urban planning as one way to foment order. The article explores plans for Bogotá developed by Le Corbusier, Josep Lluis Sert, and Paul Lester Wiener first by analyzing ideas related to their professional organization, the Congrès Internationaux d’Architecture Moderne (CIAM). It then turns to the planning process, which became increasingly complicated in the late 1940s and early 1950s, amidst ongoing violent conflict, repression, and urban migration. The plans ultimately foundered on practical issues and opposition by Colombian actors, including officials and business interests. The article considers utopianism in political context and posits the historical importance of plans that are never enacted.